INTRAPARTUM ASPHYXIA AND NEONATAL HYPOXIC-ISCHEMIC ENCEPHALOPATHY: PATHOPHYSIOLOGICAL BASES, DIAGNOSIS, AND CLINICAL MANAGEMENT - Vargas-Vera, Ramón Miguel; Placencia-Ibadango, Martha; Alencastro-Placencia, Jocelyn Maribel; Flores-Luna, Ana María; Salazar, César William Luciano; Campos-Carbo, Lito Danny; Erazo-Flores, Norma Matilde; Vargas-Silva, Kathiuska Stefany; Mero-Sánchez, Allison Deyalit; Castro, Paul Vilchez (Seven Editora, 2026)
Perinatal asphyxia and neonatal hypoxic-ischemic encephalopathy are among the leading causes of neonatal morbidity and mortality and long-term neurological disability worldwide. This condition results from impaired gas exchange leading to hypoxemia, hypercapnia, and metabolic acidosis, triggering a pathophysiological cascade characterized by cellular energy failure, excitotoxicity, oxidative stress, inflammation, and neuronal apoptosis. The incidence is higher in low- and middle-income countries, and its etiology is multifactorial, including intrapartum hypoxic events as well as prenatal and postnatal factors. Clinically, it manifests with altered level of consciousness, hypotonia or hypertonia, neonatal seizures, and multiorgan involvement. The Sarnat classification allows stratification of severity and helps guide prognosis. Diagnosis requires a multimodal approach integrating clinical assessment, blood gas analysis, electroencephalographic monitoring, and neuroimaging, with magnetic resonance imaging being the gold standard for detecting early brain injury. Treatment is based on intensive support and neuroprotective strategies, with early-initiated therapeutic hypothermia standing out as an intervention that reduces mortality and neurological sequelae in moderate to severe cases. However, therapeutic limitations persist, and new alternatives such as erythropoietin, melatonin, and cellular therapies are under investigation. Prognosis depends on clinical severity, neuroimaging findings, and electroencephalographic evolution. In conclusion, neonatal hypoxic-ischemic encephalopathy remains a significant clinical challenge, requiring timely prevention and comprehensive multidisciplinary management. Furthermore, long-term follow-up is essential to detect neurodevelopmental impairments and optimize rehabilitation interventions and comprehensive family support, improving functional outcomes in childhood.